Media Literacy in Modern Education: Problems and Achievements of Scholars - Романюк, Світлана (My University, 2021)
The article on the basis of systematic retrospective analysis of domestic and foreign scientific literature and modern educational realities, substan tiates the relevance of the formation of media literacy of the individual in the information society. Since the media ambiguously affect the spiritual world of a person, the education of the younger generation, its integration into society, it is necessary to teach children and young people to adequately perceive, analyze and evaluate broadcast information and use it wisely in their lives. The views of scientists from different countries on the essence of the concepts of media education and media literacy, which entered into the scientific circulation and educational space in the 30s of the twentieth cen tury and are aimed at the perception of a diverse information, to prepare growing generation for life in modern information conditions, to teach people to communicate verbal and nonverbal forms of communication through technical means. Emphasis is placed on the need to start the formation of media literacy in primary school, in particular during the study of the content line “Exploring the media” in the lessons of language and literature. It analyzes the ways of carrying out this process and the components of ineffective literacy, as well as various forms of organization of educational activities of primary school students, the use of which allows to develop critical thinking and media competence of students. Theoretical considerations are confirmed by me thodical developments in the study of the topic “Fairy tales from around the world” in the lessons of “Literary reading” (“Ugly duckling”, “Mitten”, “Bunny fairy tale”, etc.) using media. It is argued that the development of media literacy and media culture is an extremely important factor in shaping the moral and ethical qualities and civic position of primary school students of the New Ukrainian School, which integrates today into the uropean and world educational space.
Keywords: Media Literacy; development; innovative technologies; literary reading; language and literature branch